Implementasi Program Simpan Pinjam Perempuan Di Desa Mendawai Kecamatan Mendawai Kabupaten Katingan: Implementing women's lending program Mendawai village of mendawai subdistrict Regency of katingan - Masrukin, Masrukin; Fitriadi, Nur Akhsan (Pencerah Publik, 2018)
This study focused on implementing the Program of the women's borrow in Mendawai village, Mendawai District, Katingan Regency. The purpose of this research is to know how the implementation of the Save women's Program and the supporting factors and supporters of the women's Save borrow program in the village Mendawai District Mendawai District Katingan. In the study that raised the title of implementation of the women's Save lending Program, the method of research was taken using qualitative methods. The data obtained in this research is gathered through interviews, observations, and documentation. The results showed that in the program of the women's borrowing in Mendawai village, Mendawai District, Katingan District, there are constraints of UPK and the members of the loan. The advice that researchers can give to the parties to the implementation of this female borrow is (1) It is expected to be aware of the constraints in implementing the women's Save (SPP) program for the Women's Save loan ( The SPP) can go well. (2) Hopefully UPK should be able to put the data of each group to the computer so that if the group will make loans in the second period of the community group no longer have to complete the requirements such as the first period (3) be expected For the problem of facility should UPK also pay attention to office conditions as supporting the performance of its members.